Adaptation of urban infill housing towards malaysian city centre revitalisation - Liew, Toh Yean (2006)
Infill development, especially residential or mixed-use infill, is one of the central planning challenges in the decades ahead. Infill offers many benefits when compared with "greenfield" suburban development: it can reduce sprawl, preserve open space, revitalize downtowns and older neighbourhoods, create more walkable, transit-oriented communities, improve job, housing imbalances, reduce infrastructure expenses, and provide residents with a greater variety of housing options. Not surprisingly, infill figures prominently in Smart Growth, Sustainable Development , and New Urbanist agendas. This research is about making and maintaining pleasant places to live against the forces of sprawl. This research is timely and vital if we want to improve our urban living qualities. Currently in Malaysia, development tends to sprawl out into suburban areas with mega housing schemes. There are infill developments haphazardly developed in inner cities for high income residentials. Although there are some guidelines or regulations to monitor infill development , these are still superficial and not being rationalized. In searching for better ways to develop our city centres into a community living areas, the research learned from other countries experiences and adapting the best practices and as well exploring on appropriate innovative ideas for the Malaysian Context. A case study in Kuala Lumpur is taken to understand the strength and weaknesses in development mechanism. It is done through chronological document review. At the end of the research, some ideas to rectify the current weaknesses with good practices learned from American and British are presented